Sterling, European monetary unification, and the international monetary system - Cooper, Richard N. (London : British-North American Committee, 1972)
This paper was drafted in 1971 after the German mark had been floated. It also deals with Werner Plan for monetary unification in Europe and the problem of reliance of U.S dollar as centerpiece of financial system.
Includes bibliographical footnotes.
usc 30/06/2017
Loans
Keywords: Monetary unions; Monetary policy; Foreign exchange; Sterling area